2022
DOI: 10.1002/ps.7113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating invasion risk and population dynamics of the brown marmorated stink bug across the contiguous United States

Abstract: BACKGROUND Invasive species threaten the productivity and stability of natural and managed ecosystems. Predicting the spread of invaders, which can aid in early mitigation efforts, is a major challenge, especially in the face of climate change. While ecological niche models are effective tools to assess habitat suitability for invaders, such models have rarely been created for invasive pest species with rapidly expanding ranges. Here, we leveraged a national monitoring effort from 543 sites over 3 years to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 108 publications
1
8
0
Order By: Relevance
“…Adult longevity of H. halys from the current study falls within the lower range when compared to other studies [ 4 , 14 , 15 ]. Such differences might depend on factors including diet, adaptation of species to certain climatic conditions, and genetic background [ 24 , 25 , 26 , 27 ]. The data from the current study are however comparatively similar and within realistic developmental parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult longevity of H. halys from the current study falls within the lower range when compared to other studies [ 4 , 14 , 15 ]. Such differences might depend on factors including diet, adaptation of species to certain climatic conditions, and genetic background [ 24 , 25 , 26 , 27 ]. The data from the current study are however comparatively similar and within realistic developmental parameters.…”
Section: Discussionmentioning
confidence: 99%
“…These comparative and unique parameters of H. halys can be used to explore possible scenarios at a range of temperature extremes and help researchers in the future to strategize their pest control methods. Population distribution and seasonal estimation models have been developed [ 9 , 27 ] for H. halys but can likely be elaborated and refined with the addition of the parameters from these studies.…”
Section: Discussionmentioning
confidence: 99%
“…While these models helped with our understanding of potential spread on a global scale, they did not give sufficiently detailed predictions for integrated pest management purposes as correlations between output scores from ENMs and mean abundance have been inconsistent or weak (VanDerWal et al 2009, Osorio-Olvera et al 2019). A newer approach for H. halys (Illán et al 2022) has been to combine the use of an ENM to predict and identify the factors mediating occurrence with a generalized boosted model to predict and identify factors mediating abundance. This approach demonstrated that the factors that are most influential for the former need not be the same as for the latter.…”
Section: Discussionmentioning
confidence: 99%
“…35 The maximum entropy algorithm (MaxEnt 3.4.4), one of the most commonly used ENM algorithms was chosen due to its robust performance consistently demonstrated in numerous previous studies. 36,52,53 For both NA and CM ranges, we randomly generated 10 000 background points within each range. Then, we combined 70% of the thinned occurrence data and the data for seven environmental variables under historical climatic scenarios belonging to corresponding ranges to calibrate NA models and CM models, respectively, using the rest for model evaluation.…”
Section: Ecological Niche Modeling For D Valensmentioning
confidence: 99%